ANALISIS MOTIVASI BERPRESTASI ATLET BULUTANGKIS DI KABUPATEN BUNGO - GHAZALI INDRA PUTRA JHONY HENDRA (FKIP UMSB, 2017)
The purpose of this research was to analyze and describe the achievement motivation of badminton athletes in Bungo district. This research has shown some of its outcome target such as becomes a topic discussion in local scientific meeting which has been held in STKIP-MB. In addition, the results of this study will be published in the National Journal of ISSN. Furthermore, this research was a qualitative research with descriptive method. The data were gathered through observation, interview and documentation study. Sources of data in this study were athletes and badminton coaches who joined in the bottom club PBSI Bungo. This research was conducted in June 2017 until August 2017. The conclusions of this research were: (1) motivation source for achievement of badminton athletes in Bungo was the intrinsic motivation. They wanted to be excellent athletes, champion and top athlete, (2) even though the motivational role of the badminton athlete of Bungo district in PB Bungo Sport and PB Tunas Bungo was high, but it could not contribute to the achievement. This happened due to coaches, parents and related parties didn’t fully support the athlete's process while training for the match.Keywords: Achievement motivation, badminton athlete